As práticas farmacológicas com o metilfenidato : habitando fronteiras entre o acesso e o excesso - Domitrovic, Nathalia (2014)
Methylphenidate is the main drug indicated for the treatment of Attention Deficit and Hyperactivity Disorder (ADHD) and it is currently present in the scientific discourse as well as in the midiatic and general-people discourse. Its high levels of consumption around the world, in continuous expansion, have caused polemical discourses, full of controversies. Based on Foucault"s idea that objects and subjects are not closed essences, but are continuously produced by the intersection of practices, this study aims to produce a cartography of the various practices involving methylphenidate usage, understanding that these act as vectors of subjectivation and take part in the construction of realities and ways of living. Thus, we name this set "pharmacological practices", in reference to a network of elements that include from the consumption, to the academic and scientific productions, the midiatic discourses, the political games, everyday dilemmas of users and their families, the pharmaceutical industry economic interests, the daily lives of public policies and services, among others. The given analysis is done at three dimensions. Firstly, we have conducted a historical study, from the advent of psychiatric drugs to the emergence of methylphenidate as the consumption phenomenon currently known. After that, we have analyzed the recent publication of the new methylphenidate dispensing protocol by the Health Department of São Paulo, problematizing the challenge of thinking this drug the scope of Public Policies. And finally, we bring our field experience, reporting the paths of a research-intervention up to its most recent phase: performing groups, at CAPSi - Vitória, with healthcare workers and with families of children under methylphenidate, making use of the Brazilian Guide to Autonomous Management of Medication (GGAM-BR). The Analyses of the memories of the GAM group meetings point to the opening in the communication coefficient between users, families and healthcare workers, strengthening co-management practices in conducting Therapeutic Projects of the children involved as well. They also indicate new challenges for the continuity of the research process with the GAM strategy at CAPSi Vitória.